2017
DOI: 10.1089/tmj.2016.0192
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Provider Satisfaction with Teledermatology

Abstract: Patients and dermatologists prefer in-person examinations and diverge on preferring store-and-forward and live interactive when video is not compressed. The amount of video compression that can be applied without noticeable image degradation is a question for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 31 publications
4
66
0
1
Order By: Relevance
“…Perceived usefulness and perceived ease of use are constructs that are integral to the adoption of technology [23, 29]. Our results were similar to two previous studies that assessed the acceptance of consumer-driven mobile teledermoscopy [9, 25]. The first study assessed the acceptance of conducting mobile teledermoscopy in the home environment for the early detection of melanoma ( n = 228).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Perceived usefulness and perceived ease of use are constructs that are integral to the adoption of technology [23, 29]. Our results were similar to two previous studies that assessed the acceptance of consumer-driven mobile teledermoscopy [9, 25]. The first study assessed the acceptance of conducting mobile teledermoscopy in the home environment for the early detection of melanoma ( n = 228).…”
Section: Discussionsupporting
confidence: 81%
“…In the second study, a small pilot group of 10 participants found the dermatoscope easy to use [10]. In another study, Marchell et al [25] conducted both face-to-face ( n = 206) and teledermoscopy ( n = 209) performed by a medical practitioner and found that participants preferred face-to-face over teledermoscopy. However, overall satisfaction with teledermatology was still high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample sizes of the studies ranged between eleven and 475 (mean = 165.8; median = 126.0). In five studies, S&F was investigated in addition to LI, of which two report results of the same project . One study included telepsychology in addition to teledermatology .…”
Section: Resultsmentioning
confidence: 99%
“…We identified 23 studies that met eligibility criteria. Eleven studies were carried out in the Unites States, 18,[22][23][24][25][26][27][28][29][30][31] four studies in the UK 13,14,32,33 and two studies in Norway. 34,35 One study each was conducted in Spain, 12 Canada, 36 New Zealand, 37 India 38 and Singapore.…”
Section: Study Characteristicsmentioning
confidence: 99%